The Rise of the CRISPR/Cpf1 System for Efficient Genome Editing in Plants - Alok, Anshu; Sandhya, Dulam; Jogam, Phanikanth; Rodrigues, Vandasue; Bhati, Kaushal K.; Sharma, Himanshu; Kumar, Jitendra (Frontiers in Plant Science, 2020)
Cpf1, a single RNA-guided endonuclease of a class 2 CRISPR family, which fills the gaps that were faced previously in the world of genome engineering tools such as TALEN, ZFN, and CRISPR/Cas9. Other tools were not able to do re engineering at the same region, due to the loss of target site after first time engineering. Cpf1 acts as a dual nuclease, functioning as an endoribonuclease to process crRNA and endodeoxyribonuclease to cleave target sequences and generate double-stranded breaks. Cpf1 allows for multiplexed genome editing, as a single crRNA array transcript can target multiple loci in the genome. CRISPR/Cpf1 system enables gene deletion, insertion, base editing, and locus tagging in monocot as well as in dicot plants with less off-target effect. This tool has been efficiently demonstrated into tobacco, rice, soybean, and wheat etc. This review covers the development and applications of Cpf1 mediated genome editing technology in plant.